Cross-racial class protest in antebellum American literature - Helwig, Timothy (Amherst : University of Massachusetts Press, 2020)
"Historians have long claimed that the antebellum white working class viewed blacks, both free and slave, not as allies but enemies. While it is true that racial and ethnic strife among northern workers prevented an effective labor movement from materializing in America prior to the Civil War, Cross-Racial Class Protest in Antebellum American Literature demonstrates that a considerable subset of white and black writers were able to imagine cross-racial solidarity in the sensation novels and serial fiction, slave narratives, autobiographies, speeches, and newspaper editorials that they penned. Timothy Helwig analyzes the shared strategies of class protest in popular and canonical texts from a range of antebellum white and black American authors, including George Lippard, Ned Buntline, Harry Hazel, Frederick Douglass, William Wells Brown, and Frank J. Webb. This pathbreaking study offers original perspectives on racial representations in antebellum American print culture and provides a new understanding of black and white authors' strivings for socioeconomic justice across racial lines in the years leading up to the Civil War"--
Black and White Artisan Heroes -- The Class Accents of Anti-Slavery Reform -- The Cross-Racial Appeal of Nativism -- Class-Accented Sensationalism in the Black and Popular Presses -- Coda.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Universidad Sergio Arboleda; American literature -- 19th century -- History and criticism; Working class in literature; Social classes in literature; Race relations in literature; African Americans in literature; Working class writings, American -- History and criticism; Littérature américaine -- 19e siècle -- Histoire et critique; Travailleurs dans la littérature.; Classes sociales dans la littérature.; Relations raciales dans la littérature.; Noirs américains dans la littérature.; Écrits d'ouvriers américains -- Histoire et critique; LITERARY CRITICISM -- General; African Americans in literature; American literature; Race relations in literature; Social classes in literature; Working class in literature; Working class writings, American; Arbeiter; Arbeiterliteratur; Ethnische Beziehungen; Literatur; Schwarze; Schwarze; Soziale Klasse; 1800-1899; Criticism, interpretation, etc